2014
DOI: 10.1371/journal.pone.0112047
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Effector Functions of Human RSV-Specific IgG from Bovine Milk

Abstract: BackgroundRespiratory syncytial virus (RSV) infection is the second most important cause of death in the first year of life, and early RSV infections are associated with the development of asthma. Breastfeeding and serum IgG have been shown to protect against RSV infection. Yet, many infants depend on bovine milk-based nutrition, which at present lacks intact immunoglobulins.ObjectiveTo investigate whether IgG purified from bovine milk (bIgG) can modulate immune responses against human RSV.MethodsELISAs were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…1 and Supplementary Table 1 ), and multiple F-directed antibodies can neutralize both hRSV and bRSV. 21 24 Based on the success of our prior engineering of pre-F hRSV F trimer, 17 we modified bRSV F to create thermostable pre-F trimers. A disulfide between residues 155 and 290 (DS) along with cavity-filling mutations S190F and V207L (Cav1) and a C-terminal T4-phage fibritin trimerization domain (foldon) were incorporated into bRSV F from seven different strains to make bovine versions of DS-Cav1 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Supplementary Table 1 ), and multiple F-directed antibodies can neutralize both hRSV and bRSV. 21 24 Based on the success of our prior engineering of pre-F hRSV F trimer, 17 we modified bRSV F to create thermostable pre-F trimers. A disulfide between residues 155 and 290 (DS) along with cavity-filling mutations S190F and V207L (Cav1) and a C-terminal T4-phage fibritin trimerization domain (foldon) were incorporated into bRSV F from seven different strains to make bovine versions of DS-Cav1 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the effect shown after TLR7/8 re-stimulation, bIgG was also able to induce trained immunity when re-stimulated with TLR4, but not with TLR1/2. Bovine Immunoglobulin G is known to bind to human monocytes, macrophages, and monocyte-derived dendritic cells via FcyRII (CD32 receptor) [ 49 ]. Den Hartog et al showed that bIgG could bind to human airway pathogens, such as respiratory syncytial virus (RSV), haemophilus influenzae type b (Hib) and influenza virus [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine Immunoglobulin G is known to bind to human monocytes, macrophages, and monocyte-derived dendritic cells via FcyRII (CD32 receptor) [ 49 ]. Den Hartog et al showed that bIgG could bind to human airway pathogens, such as respiratory syncytial virus (RSV), haemophilus influenzae type b (Hib) and influenza virus [ 49 ]. These pathogens can activate TLR2 and TLR4 (Hib and RSV), TLR7 (RSV and influenza) and TLR8 (RSV) [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… Human (Heikkila and Saris 2003 ; Hunt et al 2011 ; Martin et al 2009 ) IgA Humoral immunity/modulates microbiota composition Human (Rogier et al 2014 ; Rogosch et al 2012 ; Wolf, et al 1994 , 1996 ) Raw cow milk/ bIgG Recognizes pathogens that can also infect humans (e.g. RSV) Human (den Hartog et al 2014 ) Collostrum bIgG Reduces recurrent diarrhea in AIDS patients Human (Floren et al 2006 ) Lactoferrin, lactoperoxidase and lysozyme Protects low birth weight infants from necrotizing enterocolitis Human (Manzoni et al 2014 ) Vitamin A Establishes normal levels of type 3 (RORγT + ) intestinal lymphoid cells Mice (Spencer et al 2014 ) Retinoic acid (+ TGF-β) Promotion of Tregs via CD103 + DCs Human/mice (Coombes et al 2007 ; den Hartog et al 2013 ) Retinoic acid Inhibits Th17/converts Tregs to T follicular helper cells/upreg. CCR9 and α4β7 Mice (Benson et al 2007 ; Iwata et al 2004 ; Mora et al 2003 ; Mucida et al 2007 ; Sun et al 2007 ...…”
Section: Fetal Lifementioning
confidence: 99%
“…The active form of bovine TGF-β2 (the predominant cytokine in milk) is even 100 % identical to human TGF-β2, and bovine IL-10 is fully comparable to human IL-10 in its anti-inflammatory effects of human monocytes and dendritic cells (Chatterton et al 2013 ; den Hartog et al 2011 ). Bovine IgG can bind to human Fc gamma receptors on monocytes and neutrophils (den Hartog et al 2014 ; Kramski et al 2012 ), and bovine IgG recognizes a wide range of pathogens that can also infect humans such as respiratory syncytial virus (den Hartog et al 2014 ; Xu et al 2006 ). Bovine colostrum, that is extremely rich in bovine IgG, has been shown to significantly reduce recurrent diarrhea in AIDS patients, showing that bovine IgG can have an anti-pathogenic effect in humans (Floren et al 2006 ).…”
Section: Dietary Exposure and Host Immunity In Early Lifementioning
confidence: 99%